2021
DOI: 10.1103/physrevmaterials.5.016001
|View full text |Cite
|
Sign up to set email alerts
|

Interference effects in high-order harmonics from colloidal perovskite nanocrystals excited by an elliptically polarized laser

Abstract: Halide perovskite nanocrystals are suitable materials for photonic devices because their highly efficient luminescence can be tuned over a wide wavelength range by changing the nanocrystal composition and size. Here, we report on the high-order harmonic generation in a solution-processed perovskite CsPbBr 3 nanocrystal film that is excited by a strong midinfrared laser. We observe harmonics up to the 13th order, which is ultraviolet light well above the band-gap energy. By using elliptically polarized laser li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 47 publications
(60 reference statements)
0
14
0
Order By: Relevance
“…Hence, several researchers focused on demonstrating HHG from various solid and liquid elements. 106,107 The laser intensity utilized in the experiments is constrained because of the damage threshold to the solid. The photon energy resulting from this method is not particularly high.…”
Section: Application Of Pscs Toward the Generation Of High-order Harm...mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, several researchers focused on demonstrating HHG from various solid and liquid elements. 106,107 The laser intensity utilized in the experiments is constrained because of the damage threshold to the solid. The photon energy resulting from this method is not particularly high.…”
Section: Application Of Pscs Toward the Generation Of High-order Harm...mentioning
confidence: 99%
“…Recently, strong mid-infrared laser pulses demonstrated HHG from MAPbX 3 (X = I, Br, Cl) thin films. 106,107 The near IR wavelength 800 nm is the current work-driving pulse, which possesses stronger energy than mid-infrared pulses. Therefore, there might be a chance of strong ablation leading to damage to the bulk PSCs.…”
Section: Application Of Pscs Toward the Generation Of High-order Harm...mentioning
confidence: 99%
“…Apart from the High-order MPA, the latest research also demonstrated the HHG up to 13 orders in CsPbBr 3 NC film. [137] The obtain harmonic signal has reached the regime of ultraviolet light which is well above the band-gap energy. This work also reveals that the randomness in the orientation of the…”
Section: High-order Nlomentioning
confidence: 99%
“…High harmonic generation (HHG) has been extensively investigated in the areas of extreme NLO interactions between solids, gas, and plasma plumes. The HHG process attracted the attention of researchers from the perspective of application in improvement of light sources in the extreme ultraviolet (EUV/XUV) spectral regime and attosecond photonics. Earlier works demonstrated an enhanced harmonic yield from the plasma plumes of different bulk materials, nanoparticles, and quantum dots. Recently, HHG from hybrid organic–inorganic perovskite (with a general form of MAPbX 3 , where MA = CH 3 NH 3 + and X = I, Br, and Cl) thin films exciting them with strong mid-infrared laser pulses and with linear, elliptical polarization was reported. , However, in this work, we focused on generating extreme ultraviolet radiation (10–100 nm range) from plasma plumes of pristine CsPbBr 3 and four Ni-doped CsPbBr 3 2D NCs using single-color pump (SCP) 800 nm and two-color pump (TCP) 800 + 400 nm utilizing ∼35 fs laser pulses. We firmly believe this is the first report on HHG studies from plasma plumes of CsPbBr 3 , 0.03% Ni, 0.05% Ni, 0.08% Ni, and 0.1% Ni-doped 2D NCs and correlation of enhancement of the harmonic yield with their third-order NLO coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…33−36 general form of MAPbX 3 , where MA = CH 3 NH 3 + and X = I, Br, and Cl) thin films exciting them with strong mid-infrared laser pulses and with linear, elliptical polarization was reported. 37,38 However, in this work, we focused on generating extreme ultraviolet radiation (10−100 nm range) from plasma plumes of pristine CsPbBr 3 and four Ni-doped CsPbBr 3 2D NCs using single-color pump (SCP) 800 nm and two-color pump (TCP) 800 + 400 nm utilizing ∼35 fs laser pulses. We firmly believe this is the first report on HHG studies from plasma plumes of CsPbBr 3 , 0.03% Ni, 0.05% Ni, 0.08% Ni, and 0.1% Ni-doped 2D NCs and correlation of enhancement of the harmonic yield with their third-order NLO coefficients.…”
Section: Introductionmentioning
confidence: 99%